An insight to potential application of synbiotic edible films and coatings in food products - Seyedzade Hashemi, Sahar; Khorshidian, Nasim; Mohammadi, Mehrdad (Frontiers in Nutrition, 2022)
Edible films and coatings have gained significant consideration in recent years due to their low cost and decreasing environmental pollution. Several bioactive compounds can be incorporated into films and coatings, including antioxidants, antimicrobials, flavoring agents, colors, probiotics and prebiotics. The addition of probiotics to edible films and coatings is an alternative approach for direct application in food matrices that enhances their stability and functional properties. Also, it has been noted that the influence of probiotics on the film properties was dependent on the composition, biopolymer structure, and intermolecular interactions. Recently, the incorporation of probiotics along with prebiotic compounds such as inulin, starch, fructooligosaccharide, polydextrose and wheat dextrin has emerged as new bioactive packaging. The simultaneous application of probiotics and prebiotics improved the viability of probiotic strains and elevated their colonization in the intestinal tract and provided health benefits to humans. Moreover, prebiotics created a uniform and compact structure by filling the spaces within the polymer matrix and increased opacity of edible films. The effects of prebiotics on mechanical and barrier properties of edible films was dependent on the nature of prebiotic compounds. This review aims to discuss the concept of edible films and coatings, synbiotic, recent research on synbiotic edible films and coatings as well as their application in food products.